1986
DOI: 10.1080/01688638608401311
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-year stability of some neuropsychological tests in learning disabled subjects with and without neurological impairment

Abstract: The stability of the WISC/WAIS-R and seven other commonly used neuropsychological tests over a period of 15 years was investigated in 133 learning-disabled subjects, and for subgroups with hard neurological signs, soft neurological signs, and without neurological findings. Results showed high and significant correlation coefficients between time 1 (mean age 10 years) and time 2 (mean age 25 years), even though for some tests a change from the children's to the adult version occurred. Using a repeated-measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
2
6
0
Order By: Relevance
“…43-44). Results from this study are consistent with previous research in terms of the difference between altered forms of the Category Test (Beaumont, 1975;Kupke, 1983;Maclnnes et al, 1981;Miller, 1989), the relationship between neuropsychological impairment and Category Test performance (Boyle, 1988;Charter et al, 1987;Corrigan et al, 1987;Davidoff et al, 1985;Everett, 1984;Goldstein, 1990;Horton & Siegel, 1990;Matarazzo et al, 1974;Matarazzo et al, 1976;Moses, 1985;Pendleton & Heaton, 1982;Roth et al, 1989;Sarazin & Spreen, 1986), the relationship between neuropsychological impairment and the WAIS-R intelligence quotients and factor scores (Bigler et al, 1981;Brooks, 1983;Chadwick et al , 1981b;Jennett, 1986;Levin et al , 1982;Levin & Eisenberg, 1979), and the suspected neuropsychological functions tapped by the Category Test (Boyle, 1988;Golden et al, 1981;Halstead, 1947;Klonoff, 1971;Lansdell & Donnelly, 1977;Nussbaum & Bigler, 1989;Rattan et al, 1986;Reitan & Wolfson, 1985;Rothke, 1986;Swiercinsky, 1979) . Despite these consistencies, however, several considerations should be noted regarding this study.…”
Section: Chapter IV Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…43-44). Results from this study are consistent with previous research in terms of the difference between altered forms of the Category Test (Beaumont, 1975;Kupke, 1983;Maclnnes et al, 1981;Miller, 1989), the relationship between neuropsychological impairment and Category Test performance (Boyle, 1988;Charter et al, 1987;Corrigan et al, 1987;Davidoff et al, 1985;Everett, 1984;Goldstein, 1990;Horton & Siegel, 1990;Matarazzo et al, 1974;Matarazzo et al, 1976;Moses, 1985;Pendleton & Heaton, 1982;Roth et al, 1989;Sarazin & Spreen, 1986), the relationship between neuropsychological impairment and the WAIS-R intelligence quotients and factor scores (Bigler et al, 1981;Brooks, 1983;Chadwick et al , 1981b;Jennett, 1986;Levin et al , 1982;Levin & Eisenberg, 1979), and the suspected neuropsychological functions tapped by the Category Test (Boyle, 1988;Golden et al, 1981;Halstead, 1947;Klonoff, 1971;Lansdell & Donnelly, 1977;Nussbaum & Bigler, 1989;Rattan et al, 1986;Reitan & Wolfson, 1985;Rothke, 1986;Swiercinsky, 1979) . Despite these consistencies, however, several considerations should be noted regarding this study.…”
Section: Chapter IV Discussionsupporting
confidence: 82%
“…This is consistent with previous research that indicates the total error score on the Category Test effectively discriminates brain-injured from non-brain-injured individuals (Boyle, 1988;Charter et al, 1987;Corrigan et al, 1987;Davidoff et al, 1985;Everett, 1984;Goldstein, 1990;Horton & Siegel, 1990;Matarazzo et al, 1974;Matarazzo et al, 1976;Moses, 1985;Pendleton & Heaton, 1982;Roth et al, 1989;Sarazin & Spreen, 1986).…”
Section: Chapter IV Discussionsupporting
confidence: 81%
“…However, Sarazin and Spreen (1986) have provided some estimate of the reliability of various neuropsychological measures used in the assessment of children. Some of the tests they examined are included in Reitan's tests while others are independent achievement and/or neuropsychological tests.…”
mentioning
confidence: 99%
“…Some of the tests they examined are included in Reitan's tests while others are independent achievement and/or neuropsychological tests. In their investigation, Sarazin and Spreen (1986) examined a sample of children described as learning diasbled at the time of their initial assessment who were then reevaluated 9 to 17 years later as adults. The results of this investigation indicated that the most psychometrically reliable tasks in this population were measures of lateral dominance, followed by IQ tests, scholastic achievement measures, handedness surveys (writing only), and a sentence repetition test; lower reliability coefficients were observed for the Category Test, Grip Strength Test, and Right-Left Orientation Test.…”
mentioning
confidence: 99%
“…Even if test-retest reliability coefficients are high, there is however good support for the notion that Verbal IQ (VIQ) declines over the years in samples of learning-disabled (LD) and mentally retarded (MR) children (Haddad, Juliano, & Vaughan, 1994;Nichols, Inglis, Lawson, & MacKay, 1988;Stavrou, 1990;Truscott, Narrett, & Smith, 1994). As for non-verbal ability, a few studies report a decline in Performance IQ (PIQ) as well (Stavrou, 1990;Sarazin & Spreen, 1986), while others have found a reliable increase in PIQ in groups of LD children (Haddad et al, 1994;Lawson, Inglis, & Tittemore, 1987;Truscott et al, 1994).…”
Section: Introductionmentioning
confidence: 99%